1987
DOI: 10.1007/bf01892358
|View full text |Cite
|
Sign up to set email alerts
|

Assay of some nutritional and antinutritional factors in different cultivars of winged bean (Psophocarpus tetragonolobus (L.) DC) seeds

Abstract: Seed of 34 cultivars of winged bean of different origin were evaluated for their nutritional composition and the antinutritional factor, the trypsin inhibitor. The values ranged from 14.1 17.6, 6.12-8.73, 21.94-34.89 and 30.86-39.05% for their fat, fibre, carbohydrate and protein contents, respectively. The protein content in defatted seed meal ranged from 33.4347.25%, whereas the trypsin inhibitor activity (TIA) registered a wide variation from 63-123 mg g-t with seed coat and 51-98 mg g-1 without seed coat. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…ese results are similar to those of previous studies that reported between 23 and 40% [4,22] and 28.87 ± 0.45 in a study conducted by Wan Mohtar et al [3], but low when compared to other studies involving cowpea and wheat flours, where values ranged from 57.35% to 83.60% [23] with wheat flour having the highest carbohydrate content (83.60%). In this study, the carbohydrate content of the flours cannot be compared to that of cowpea (57.17%) and wheat flours (74.22%) reported by Ahmed et al [24].…”
Section: Discussionsupporting
confidence: 90%
“…ese results are similar to those of previous studies that reported between 23 and 40% [4,22] and 28.87 ± 0.45 in a study conducted by Wan Mohtar et al [3], but low when compared to other studies involving cowpea and wheat flours, where values ranged from 57.35% to 83.60% [23] with wheat flour having the highest carbohydrate content (83.60%). In this study, the carbohydrate content of the flours cannot be compared to that of cowpea (57.17%) and wheat flours (74.22%) reported by Ahmed et al [24].…”
Section: Discussionsupporting
confidence: 90%
“…the cultivar (Prakash et al 1991;Vasconcelos et al 1997), maturity (Prakash et al 1991), fermentation (Barimalaa et al 1994), and heat treatment (Ros and Collins 1992;Carvalho and Sgarbieri 1997). The presence of trypsin inhibitor affects the protein efficiency ratio for the consumer as well as agronomic characteristic for the plants (Misra et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Winged bean plant is appreciated for the high nutrients composition, especially with respect to proteins, vitamins and minerals; the tubers are starchy with high percentage of proteins 17 to 20% (by weight) compared to other vegetables, the leaves and flowers contain from 5 to 15% proteins (by weight), the seeds are highly nutritious with 32 to 37% proteins, which is similar to the amount of proteins found in soy beans and higher than that found in other beans [26]. The seeds also contain 23 to 40% carbohydrates [8,28,29], vitamins like vitamin B 1 , B 2 , B 3 , B 6 , B 9 and in vitamins C, A and E. The mature seeds contain 14 to 25% fats by weight, of which 94% are in free form, whereas the rest are complexed with carbohydrates and proteins [29].…”
Section: Nutrient Compositionmentioning
confidence: 88%
“…Winged bean is rich in minerals including calcium, iron, phosphorous, potassium, sulfur, sodium, magnesium, zinc, manganese, boron, barium, copper, chromium and strontium [28,30,31]. Psophocarpus tetragonolobus contains 54 to 75% of unsaturated fatty acids, of which 38.6% are mono-unsaturated and 36.9% are polyunsaturated [29,32], and no trans fatty acids are found.…”
Section: Nutrient Compositionmentioning
confidence: 99%